Formulation and Evaluation of Natural Oil (Turmeric and Chenopodium Oil Nanoemulsion for Effective Treatment of Cancer - Mukul Singh; Md Sarfaraz Alam; Satyendra Kumar Mishra; Pushkar Kumar Ray; Mohammed Abdullah Alasmari; Khalid Manea Alotaibi; Ali A. Alhafi; Ghaleb S. Alharbi; Noureldaim Elnoman Elbadawi Mohamed; Nehal Mohsin; et al. (The Bioscan, 2024)
Background: Turmeric oil and Chenopodium oil are natural oils with much evidence for their therapeutic actions including anticancer activity. Aim: Present studied was to explore the anticancer activity of nanoemulsion prepared by Turmeric and Chenopodium oil. Method: Tu-Ch oil nanoemulsion prepared using Tween 80 by ultrasonication. The anticancer activity of Nanoemulsion estimated by MTT cell viability assay against HeKa Toungue carcinoma cells. Results: To increase the stability of essential oils through Nanoemulsion. The optimized formulation of Nanoemulsion was studied at increased (oil: surfactant) ratio and evaluation by analysis of PH, Viscosity, Zeta potential, Poly dispersity index, particle size distribution, and cell viability at different concentrations. The particle size of developed nanoemulsion (A2) was found to be 172.3 nm, viscosity of the nanoemulsion formulation was (28.55 ± 2.03mP) and Zeta potential was 0.240 ± 0.05, PDI value -28.0± 0.24 for Tu-Ch oil-loaded nanoemulsion. turmeric oil and chenopodium oils together in nanoscale showed a concentration- dependent cytotoxicity effect. Conclusion: This study proves that the Combination of Turmeric and Chenopodium Oil nanoemulsion is a permissible natural medicine that can overcome the drawbacks in cancer treatment.